28. Treatment with onabotulinumtoxinA of pectoral spasm after expander-based breast reconstruction. Issue 4 (April 2016) - Maderna, L.; Doretti, A.; Riccardi, B.; Gregorini, F.; Gerevini, S.; Silani, V.
Abstract : Breast reconstruction tissue expander-based is the most common technique used for reconstruction after radical mastectomy for cancer. Breast reconstruction with fat grafting (FAT transfer) is a technique widely used in current practice. 62-year-old woman has been subjected to mastecmia and subsequent reconstructive surgery of the breast expander based, retaining the expander for 10 months. After 3–4 weeks from placement of the breast implant, developed a sub-rhythmic spasm of chest muscles during standing. This spasm is persisted even after the removal of the prosthesis a year later and without any pain. She had never been subjected to chemotherapy or radiotherapy. Electromyography showed unintentional electrical activity sub-rhythmic burst with 200–250 ms, frequency 2 Hz. We have also studied the brachial plexus nerve and breastplate with magnetic resonance imaging (DTI sequences) and ultrasound of the breast region. The patient was subjected to infiltration under electromyography and ultrasound guidance of pectoralis major muscle with onabotulinumtoxinA with cramp reduction/interruption. Chest cramps is not due to nerve compression trauma implants pectoral mammal, but it should be due to the irritative activity of the graft on the pectoral nerve. In fact the spasm started after the placement of the graft.